Dampak Yuridis Sumpah Li'an Berdasarkan Hukum Islam Dan Hukum Positif - setiawan (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The process of building a household life, of course, there are many trials that arise, not a few of these trials result in a marriage relationship that has been built for years to end in court. Referring to various sources of Islamic law, there are several forms of divorce, namely: talaq, khulu`, fasakh, `ila`, li`an, zhihar, and nusyuz. When we look at the rules about marriage in the Compilation of Islamic Law (KHI), through section 116 KHI explained, that one of the causes of divorce is the existence of adultery committed by one of the parties from both husband and wife. In the event that a divorce is carried out because of adultery and then it is resolved by means of a li`an, then there are other legal consequences that will be borne by the parties, namely husband and wife and even children of both of them are affected. In this study, researchers used the library research method. The results of the research on the legal impact of the li’an Oath on wives and children according to Islamic law; husband is free from the threat of had qadzaf, adultery that the husband accuses his wife of is right, lineage of the child the wife was carrying was only related to the mother, the wife is free from the threat of adultery, li`an caused the marriage to break up forever. Meanwhile, according to positive law; li`an caused the marriage to break up forever, lineage of the child the wife was carrying was only related to the mother, and for the husband there is no obligation to provide a living.